BE_VERWALTUNGSGERICHT 100 2014 246 vom 25. Juni 2015 - BE Verwaltungsgericht (2015)
Gehaltsanspruch (Entscheid der Erziehungsdirektion des Kantons Bern vom 12. August 2014 - 4800.600.550.05/13 [645803]) | Besoldung/Entschädigung